On wheel–rail contact surface phenomena with structural changes and ‘White Etching Layers’ generation - Beneš, Libor (Transport, 2012)
The main aim of this work was a study of the microstructure transformations with the residual stress formation that is induced by rolling contact friction and adhesive wore in the wheel–rail system. Several small railsurface samples, we term them as the ‘chips’, and a piece of wheel sample were chosen for the analyses of the surface changes on the wheel–rail surface. A multitude of different experiments were carried out in order to analyse the microstructure changes at the surface and the near-surface region of the material samples and, thus, to contribute to the understanding of the complex wheel–rail rolling contact phenomena – and its degradation mechanisms. The formation of nano-structured martensite and carbides on the rail and wheel surface causes the extremely high microhardness valuees and the strong corrosion resistance of the so called White Etching Layers (WEL).First Published Online: 26 Jun 2012